2017
DOI: 10.3892/ijmm.2017.2968
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL mutant membrane penetrating peptide alike-MuR6-TR enhances the antitumor effects of TRAIL in pancreatic carcinoma both in vitro and in vivo

Abstract: Abstract.To remedy the drug resistance of natural tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and enhance its antitumor effects, we prepared a type of TRAIL mutant membrane penetrating peptide alike (TMPPA)-TRAIL mutant R6 (MuR6-TR) by mutating the N-terminal of the soluble TRAIL gene sequence. The expressed MuR6-TR protein was purified to treat pancreatic carcinoma cell lines BxPC-3 and PANC-1. The inhibitory effects on the proliferation of BxPC-3 and PANC-1 cells was assessed with CCK-8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This also explains, to some extent, why in some studies, co-culturing apoptotic tumor cells with DCs did not induce DC maturation or effectively trigger tumor-specific T cell responses ( 244 ). Enhancing the immunogenicity of apoptotic tumor cells and restoring their apoptotic activity has become a current anti-cancer strategy ( 248 , 249 ). The technique of loading specific tumor antigens into apoptotic cells to selectively activate T cell immune responses against those antigens has become an important method in studying tumor immune responses ( 250 ).…”
Section: Impact Of Efferocytosis On DC Maturation and Functionmentioning
confidence: 99%
“…This also explains, to some extent, why in some studies, co-culturing apoptotic tumor cells with DCs did not induce DC maturation or effectively trigger tumor-specific T cell responses ( 244 ). Enhancing the immunogenicity of apoptotic tumor cells and restoring their apoptotic activity has become a current anti-cancer strategy ( 248 , 249 ). The technique of loading specific tumor antigens into apoptotic cells to selectively activate T cell immune responses against those antigens has become an important method in studying tumor immune responses ( 250 ).…”
Section: Impact Of Efferocytosis On DC Maturation and Functionmentioning
confidence: 99%
“…Their results indicated that CPPs containing oligoarginine may be used to increase alveolar insulin absorption rates, while also demonstrating that covalent conjugation of insulin to r 9 was required to maximize insulin transport efficiency [172]. One of the death receptor ligands in extrinsic apoptotic signal routing that can selectively induce apoptosis in cancer cells while avoiding normal cells [140] Superoxide dismutase (SOD) Tat/Pep-1/R 9 /r 9…”
Section: Insulinmentioning
confidence: 99%
“…These results also suggest that the cell-penetrating sequence increased the binding affinity between TRAIL and the cell membrane and up-regulated DR5 to activate caspase [ 104 ]. Furthermore, the TRAIL mutant R6 (MuR6-TR) exerted a greater inhibitory effect on tumor growth than did natural TRAIL when used to inhibit activities of pancreatic carcinoma cell lines BxPC-3 and PANC-1, thus indicating that the CPP sequence may have enhanced the ability of TRAIL-Mu3 to penetrate the cell membrane without increasing cell sensitivity to TRAIL [ 140 ].…”
Section: Cpps As Vectors For Protein Delivery To Cellsmentioning
confidence: 99%